Research on the Innovative Development Model of Leisure Sports Organizations Driven by Digital Literacy - Guo, Deshun; Su , Zhanguo (International Journal of Sociologies and Anthropologies Science Reviews, 2026)
Background and Aims: Digitalization as a New Innovation in Sports: This research is an important issue. This objective study explores whether digital literacy drives innovation in leisure sports organizations in the context of the sports industry. Methodology Using a mixed-methods design, this study conducted interviews with experts and case studies to develop a conceptual framework, followed by a large-scale survey of 286 employees and managers from 48 leisure sports organizations. This research, including the Technology Acceptance Model, Resource-Based View, and Open Innovation Theory, was used to develop and validate a conceptual framework that defines digital literacy as a strategic organizational capability. Results: A quantitative analysis using Structural Equation Modeling (SEM) confirmed that digital literacy significantly enhances organizational innovation and integration, leading to a sustainable competitive advantage. Qualitative data reveal generational skill gaps, unbalanced digital strategy implementation, and the need for structured transformation programs. This study re-conceptualizes digital literacy from individual skills as a key enabler of organizations, offering a new model for guiding digital transformation in the leisure sports sector. It also provides practical recommendations for policies, training, collaboration, and strategic planning. Conclusion: This study redefines digital literacy as a critical organizational capability, not just an individual skill. By bridging generational gaps and aligning strategy, it offers a roadmap for sustainable innovation in the leisure sports sector.